Analisis Kinerja SIMRS RSU Bhakti Husada Banyuwangi Menggunakan IT Balanced Scorecard dan Model for Mandatory Use of Software Technolgies - Vivi Sefrinta Izza Afkarina; Rudi Wibowo; Saiful Bukhori (Pascasarjana Universitas Jember, 2021)
HMIS is a form of utilizing health technology to support the success of management and improvement of service quality in hospitals. The implementation of HMIS will be beneficial if its implementation is in accordance with the vision, mission, and goals of the hospital by establishing a business strategy and information technology system strategy. The purpose of this study was to analyze the performance of HMIS Bhakti Husada Hospital using the IT Balanced Scorecard and the Model for Mandatory Use of Software Technologies. This study uses a cross sectional quantitative approach with a sample of 45 respondents using HMIS. The data measured using the IT Balanced Scorecard assessment indicators were analyzed using SEM-PLS. The results showed that the HMIS performance was categorized as good. The HMIS performance achievement with the IT Balanced Scorecard with a future orientation perspective is 83.3% and an operational improvement perspective is 100%. All of the Model for Mandatory Use of Software Technologies variables have a significant influence of HMIS implementation, namely the information quality variable on information satisfaction, information satisfaction on ease of use, and ease of use on attitudes. Keywords: SIMRS, IT Balanced Scorecard, Model for Mandatory Use of Software Technologies